(untitled) (Journal of Surgical Sciences, 2019)
Penile strangulation caused by foreign bodies mostly occurs in adolescents and adult male. A man may place metal object for erotic or autoerotic purposes, for masturbation or increasing penile erection, and due to psychological disturbances which lead to penile strangulation. Penile strangulation results in reduced blood flow distal to the injury, leading to edema, ischemia, and sometimes gangrene. These injuries are divided into five grades and their treatment options are divided into four groups. Here an innovative surgical technique, which can be adopted in Grade II and Ill injury has been described. Journal of Surgical Sciences (2013) Vol. 17 (2) : 96-98